Effects of Irbesartan Pretreatment on Pancreatic β-Cell Apoptosis in STZ-Induced Acute Prediabetic Mice. (2nd December 2018) - Chen, Cuihong; Li, Li; Qin, Haijing; Huang, Zhenxing; Xian, Jing; Cai, Jinwei; Qin, Yingfen; Zhang, Jie; Liang, Xinghuan
Abstract : The current study was performed to investigate the effects and potential effects of irbesartan pretreatment on pancreatic β -cell apoptosis in a streptozotocin- (STZ-) induced acute mouse model of prediabetes. Twenty-four male BALB/C mice (18–22 g) were randomly divided into three groups: normal control group (NC, n = 6 ), STZ group (STZ, n = 8 ), and irbesartan + STZ group (IRB + STZ, n = 10 ). In the IRB + STZ group, mice were administered irbesartan (300 mg/kg per day) by gavage for one week. The STZ group and IRB + STZ group received STZ (80 mg/kg by intraperitoneal (IP) injection once). The NC group received normal saline (80 mg/kg by IP injection once). Fasting blood glucose prior to STZ injection and presacrifice was analysed using samples withdrawn from the caudal vein to confirm the induction of prediabetes. Haematoxylin and eosin staining, immunohistochemical detection of insulin, and apoptosis analysis were performed. Reverse transcription-quantitative polymerase chain reaction was used to detect angiotensin II type 1 receptor (AT1R), caspase-3, and p38 mitogen-activated protein kinase (MAPK) mRNA expression. Blood glucose was significantly higher in the STZ group (9.01 ± 1.1089 vs 4.78 ± 0.7026) and IRB + STZ group (7.86 ± 1.1811 vs 4.78 ± 0.7026) compared with the NC group (P < 0.05 ). In comparison to the STZ group, the islet cell damage was marginally improved in the IRB + STZ group, and the IRB + STZ group had a significantly lower apoptotic rate than the STZ group (22.42 ± 8.3675 vs 50.86 ± 5.3395, P < 0.001 ). AT1R expression in the IRB + STZ group was lower than that in the STZ group (1.56 ± 1.2207 vs 3.92 ± 2.4392, P < 0.05 ). The mRNA expression of caspase-3 in pancreatic tissue was significantly lower in the IRB + STZ group than in the STZ group (0.90 ± 0.7272 vs 1.88 ± 1.0572, P < 0.05 ). Similarly, the IRB + STZ group also had lower p38MAPK levels than the STZ group (1.16 ± 1.0642 vs 2.55 ± 1.7925, P > 0.05 ). In conclusion, irbesartan pretreatment improved glucose levels and insulin secretion and decreased islet β -cell apoptosis to protect islet β cells in an STZ-induced acute prediabetic mouse model.